(untitled) (Human Computation, 2014)
Archaeology has a long tradition of volunteer involvement but also faces considerable challenges in protecting and understanding a geographically widespread, rapidly dwindling and every-threatened cultural resource. This paper considers a newly launched, multi-application crowd-sourcing project called MicroPasts, whose focus is on enabling both community-led and massive online contributions to high quality research in archaeology, history and heritage. We reflect on preliminary results from this initiative with a focus on the technical challenges, quality control issues and contributors motivations.